A new species of Pseudostilobezzia Wirth & Ratanaworabhan (Diptera: Ceratopogonidae) from Vietnam - Borkent, Art; Grogan, William L. (Zootaxa, 2024)
A new species of Pseudostilobezzia Wirth & Ratanaworabhan is described, the third in this small genus, from Vietnam and based on two females. A key is provided to distinguish the three species, all restricted to the Oriental Region, in Vietnam or the nearby Hainan province, China. The phylogenetic relationship between this genus and other Ceratopogonidae suggests that it may be a somewhat distinctive lineage within Stilobezzia Kieffer. The presently unknown male of this genus will likely provide pertinent information in this regard.